BITTER MELON CHIPS AGRIBUSINESS INNOVATION AS A PRODUCT OF PROCESSED HOUSEHOLD INDUSTRY IN RURAL AREAS - Ni Putu Sukanteri; Yenni Verrawati; I Made Suryana; Gusti Ayu Diah Yuniti (Unmas Press, 2021)
The processed bitter melon home industry is one of the innovations in rural areas, in an effort to attain higher prices for agricultural products. Characteristics of perishable agricultural products, such as the commodity bitter melon, cause prices to decline after a few days of storage. KWT Ayu tangkas is a group of housewives in Megati village. Trying to innovate so that the abundant bitter melon from the garden can be marketed at a decent price and provides benefits for the family life. This research objective is to analyze the value-added commodities in the industry processed bitter melon chips and calculate the marketing margin for bitter melon chips industries in rural home processing. The research was conducted at KWT Ayu Tangkas, Megati Village, Selemadeg Timur District, Tabanan Regency. The results showed that the industry processed bitter melon gave a profit of Rp 39.000 for each production with a capacity of 5 kg bitter melon. The processing of bitter melon chips shows a value-added ratio of 85%, remuneration for the owner of the production factors shows a margin IDR 55.000. The R / C value of 1.20 indicates that every Rp. 1.00 of costs incurred in the bitter melon processing industry gives revenue of 1.20 times the costs incurred.